2015
DOI: 10.1152/ajpheart.00443.2015
|View full text |Cite
|
Sign up to set email alerts
|

Irisin improves endothelial function in obese mice through the AMPK-eNOS pathway

Abstract: Sun X. Irisin improves endothelial function in obese mice through the AMPK-eNOS pathway. Am J Physiol Heart Circ Physiol 309: H1501-H1508, 2015. First published September 14, 2015 doi:10.1152/ajpheart.00443.2015.-Irisin is a novel hormone secreted by myocytes. Lower levels of irisin are independently associated with endothelial dysfunction in obese subjects. The objective of this study was to explore whether irisin exerts a direct vascular protective effect on endothelial function in high-fat-diet-induced obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 27 publications
7
78
1
2
Order By: Relevance
“…Mice in the NC group were fed a normal chow diet and mice in the other two groups were fed a HFD (493 kcal 100 g –1 ) [18]. Mice in the irisin group were given recombinant irisin (0.5 μg/g/day; Phoenix Pharmaceuticals, Inc., Burlingame, CA, USA) by intraperitoneal injection daily [12, 14]. The other two groups were given physiological saline as control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice in the NC group were fed a normal chow diet and mice in the other two groups were fed a HFD (493 kcal 100 g –1 ) [18]. Mice in the irisin group were given recombinant irisin (0.5 μg/g/day; Phoenix Pharmaceuticals, Inc., Burlingame, CA, USA) by intraperitoneal injection daily [12, 14]. The other two groups were given physiological saline as control.…”
Section: Methodsmentioning
confidence: 99%
“…Zhu et al [10] showed that irisin improves endothelial dysfunction in diet-induced diabetic mice. In our previous study, serum irisin levels were found to be reduced in obese patients compared with non-obese subjects and that treatment of obese mice with irisin improves endothelial dysfunction by the AMP kinase (AMPK)–endothelial NO synthase (eNOS) signaling pathway [11, 12]. These findings suggest that irisin has the ability to improve endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Modified from Zhao et al 29 (Copyright ©2015, The Authors). α indicates α-adrenergic receptor; 5HT, serotonin (5-hydroxytryptamine); 5HT1d, serotoninergic (5 hydroxytryptamine) receptor 1D subtypes; ACh, acetylcholine; Ang 1-7 , angiotensin [1][2][3][4][5][6][7] ; AdipoR, adiponectin receptor; AVP, arginine vasopressin; B, kinin receptor; E, epinephrine; EP4, prostaglandin E 2 -receptor 4; ER, nongenomic estrogen receptor; ET, endothelin-1; ETb, endothelin-receptor B subtypes; GLP, glucagon-like peptide-1, glucagon-like peptide receptor; GPR55, G-protein-coupled receptor 55; H, histaminergic receptor; HDL, high-density lipoproteins; IP, prostacyclin receptor; IR 1 , insulin receptor; M, muscarinic receptor; Mas, Mas receptor; MC, melanocortin receptor; NE, norepinephrine; P, purinergic receptor; PAR, protease activated receptor; PGE 2 in a nongenomic manner on G-protein-coupled receptors), glucagon-like peptide-1, high-density lipoproteins (HDL; associating with sphingosine 1 -phosphate), insulin (by activating the PI3K/Akt pathway), irisin 52 (an autacoid/hormone secreted by myocytes), melanocortin (α-melanocyte-stimulating hormone), oxytocin, secretoneurin, 79 and vasopressin. 15 Likewise, aggregating platelets (Figure 2) release adenine nucleotides (in particular, ADP) and 5-hydroxytryptamine (serotonin), which induce endothelium-dependent relaxations.…”
Section: Blood-borne Signalsmentioning
confidence: 99%
“…This beneficial impact of exercise on endothelial vasomotor regulation, resulting from repeated augmentations in blood flow, is explained by several long-term effects of increases in shear stress that include: (1) upregulation of tyrosine kinase c-Src increasing the expression and activation (by phosphorylation) of eNOS; (2) increased production of transforming growth factor-β and subsequent activation of Krüppel-like factor-2, which promotes eNOS gene transcription; (3) upregulation of longevity-associated bactericidal permeability increasing fold-containing-family-B-member-4, the activation of which promotes the phosphorylation of eNOS at Ser1177; (4) production of endogenous hydrogen peroxide, which activates calcium/calmodulin-dependent PK II leading to activation of, on the one hand, janus kinase II upregulating eNOS expression/presence (see Reduced Protein Presence section of this article) and, on the other hand, of kinases (including Akt, AMPK, and ERK1/2), which increase phosphorylation at Ser1177 and hence activate eNOS; (5) increased production of irisin 52 ; and (6) improved mitochondrial biogenesis/function thereby permitting greater metabolic capacity (including glycolysis and oxidative phosphorylation) and preventing mitochondrial ROS formation.…”
Section: Chronic Changes In Shear Stressmentioning
confidence: 99%
See 1 more Smart Citation